Nuevos restos de ciervos (Cervidae, Mammalia) para el Pleistoceno de la Región Pampeana (Argentina): consideraciones paleobiogeográficas y paleoecológicas - Chimento, Nicolás Roberto (2019)
Cervidae are an Cetartiodactyla family that entered South America in the Pleistocene, during the event known as “Great American Biotic Exchange”. In the Argentinean Quaternary the genera Antifer, Epieuryceros, Morenelaphus and Paraceros, all extinct in the Late Pleistocene, are recognized along with the genera Hippocamelus, Pudu, Blastoceros, Ozotoceros and Mazama, present inhabitants of the South American territory, and some of which are represented also in Pleistocene times. The aim of this work is to present and describe new fossil deer remains from different Pleistocene localities in Buenos Aires Province (Argentina) and to make some geographical and environmental considerations. The southernmost record of the genus Morenelaphus and the species M. lujanensis is here presented, coming from Punta Alta locality, and the first female specimen assigned to Morenelaphus sp. is described, as well as new materials with the same assignment for the localities of Junín and Paraje 7 Bridges, Sauce Grande River Valley. New remains of Antifer sp., from San Bernardo locality, and Hippocamelus sulcatus from Junín locality are disclosed. The first Pleistocene record of Ozotoceros bezoarticus is presented for the Buenos Aires Province, coming from the Junín locality.